Optimalisasi Peningkatan Derajat Kesehatan Melalui Kegiatan Pengobatan Gratis di Kampung Pemulung Kebayoran Lama Jakarta Selatan - Redha, Pratiwi Soni; Melly Kristanti (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
The economic and social imbalance is influenced by the uneven increase in population migration across various regions. This has led to the development of informal settlements, such as the Kebayoran Lama scavenger village. These locations have altered the city's urban landscape and impacted livelihoods, particularly health. The primary occupations in this village are scavengers and garbage collectors. This encourages the provision of public health services including free medical treatment. Interviews with village leaders to obtain primary data, while secondary data were obtained from interviews with the community. Then a qualitative method was used. Attended by 110 people. Then a qualitative method was used. Attended by 110 people, consisting of 60 men and 50 women. The results of this activity found that many people experienced itching (28.1%), flu (20.2%), flu with fever (13.3%), fever (21.1%), flu with cough (9.6%). The people who participated in free treatment were more men (52.6%) compared to women (43.9%), furthermore the average age of the people who participated in free treatment was 37 years. This explains the need to increase community service efforts by providing education on clean and healthy living behaviors to improve the quality of life related to health conditions from environmental problems.